2014
DOI: 10.1891/1058-1243.23.1.41
|View full text |Cite
|
Sign up to set email alerts
|

More Than Clinical Waste? Placenta Rituals Among Australian Home-Birthing Women

Abstract: The discursive construction of the human placenta varies greatly between hospital and home-birthing contexts. The former, driven by medicolegal discourse, defines the placenta as clinical waste. Within this framework, the placenta is as much of an afterthought as it is considered the "afterbirth." In home-birth practices, the placenta is constructed as a "special" and meaningful element of the childbirth experience. I demonstrate this using 51 in-depth interviews with women who were pregnant and planning home … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 19 publications
1
23
0
Order By: Relevance
“…Apart from women who had home births, it was also reported that in some cases, placentae were taken home by women who had institutional births. This situation has also been reported in Cameroun and Australia [23] [24]. This is often tied to ethical, religious and cultural beliefs as reported here.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Apart from women who had home births, it was also reported that in some cases, placentae were taken home by women who had institutional births. This situation has also been reported in Cameroun and Australia [23] [24]. This is often tied to ethical, religious and cultural beliefs as reported here.…”
Section: Discussionsupporting
confidence: 84%
“…Based on its intrinsic value, it has been argued that placenta cannot be classified as medical waste [21] [22]. Contrariwise, the requirement for standard pre- [23]. Apart from women who had home births, it was also reported that in some cases, placentae were taken home by women who had institutional births.…”
Section: Discussionmentioning
confidence: 99%
“…The universal practice of placentophagy for perceived medical benefits distinguishes it from other practices associated with the natural birth movement (such as home births and placental burial) that are participated in from an explicit anti-medicalisation perspective [51]. Whilst Janszen concluded in [52] that placentophagy was part of the "back to nature" movement and founded on the belief that placenta consumption is common in other cultures and part of human heritage, this no longer appears to be the main motivation for the practice.…”
Section: Medicalisation Of Placentophagymentioning
confidence: 99%
“…[16][17][18] Ritualistic ceremonies surrounding the placenta are prevalent across multiple cultures. [19][20][21][22] Chinese and Egyptian historical accounts describe the placenta as having medicinal properties, used for healing and fatigue. 23,24 However, records of maternal consumption of the placenta specifically for postpartum benefits are limited.…”
Section: Introductionmentioning
confidence: 99%